Promuovere il dialogo sociale Le conseguenze dell'Europa sulla regolazione del lavoro - Alacevich, Franca (Studi e saggi, 2004)
In a very timely study resulting from analysis and comparison, the author - professor of Work Sociology at the University of Florence - captures the effects of the European Community guidelines in promoting the inclusion of social partners in decision-making processes and in the implementation of labour policies. At the same time the study identifies the processes of exchange and comparison of experiences that are leading to the formation of social and work language shared by a large community of experts from governments and social forces.